The Frontloading Approach to Meet Guideline-Recommended Visual Field Testing for Glaucoma: Time and Cost - Wang, Henrietta; Masselos, Katherine; Tan, Jeremy C K; Patel, Nimesh B; Agar, Ashish; Kalloniatis, Michael; Phu, Jack (Ophthalmology. Glaucoma, 2025)
To measure the time and clinical resources taken to obtain 6 reliable visual field (VF) tests for glaucoma in a glaucoma clinic. Longitudinal, prospective study in a glaucoma clinic. Ten thousand and ten SITA-Faster VF tests of 535 clinical subjects. The cumulative number of VF tests with false-positive rates ≤15% for each eye of each subject was counted over time, and from there, the time to achieve 6 VF tests was determined and compared under frontloaded (2 VFs per eye per visit) and non-frontloaded (first VF within the frontloaded set) conditions. Costs to attain 6 VF tests were modeled. Visual field counts and costs for attainment. Eight thousand nine hundred thirty-one of the 10 010 VF results had a false-positive rate of ≤15%. Approximately 90% of subjects had early or moderate open-angle glaucoma. When using the frontloading protocol, it took an average of 1.4 years to attain 6 reliable VFs for right and left eyes, respectively. For the non-frontloaded protocol, the average times were 2.6 and 2.5 years for the right and left eyes, respectively; 82.5% of right eyes and 85.4% of left eyes achieved 6 reliable VFs within 2 years when frontloaded, but the proportion was only 15.8% and 18.8% when non-frontloaded for right and left eyes, respectively. There was a significantly lower cost for obtaining 6 reliable VFs with frontloading than non-frontloading, due to fewer office visits. A frontloading approach and SITA-Faster paradigm led to patients attaining 6 reliable VFs over 14 months sooner than non-frontloaded, with >84% receiving the recommended number of 6 tests in the first 2 years. The frontloading approach overall leads to savings in time and cost in comparison to non-frontloading for achieving 6 reliable VFs and thus potentially provides an avenue for earlier detection of glaucomatous change. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.